2022
DOI: 10.1007/s00705-022-05417-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel gyrovirus in a common pheasant (Phasianus colchicus) with poult enteritis and mortality syndrome

Abstract: A novel gyrovirus was detected in an intestinal specimen of a common pheasant that died due to poult enteritis and mortality syndrome. The genome of the pheasant-associated gyrovirus (PAGyV) is 2353 nucleotides (nt) long and contains putative genes for the VP1, VP2, and VP3 proteins in an arrangement that is typical for gyroviruses. Gyrovirus-specific motifs were identified in both the coding region and the intergenic region of the PAGyV genome. The VP1 of PAGyV shares up to 67.6% pairwise nt sequence identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In recent years, other circoviruses have been reported, and several species have been shown to be pathogenic to poultry ( Truchado et al, 2019 ; Feher et al, 2022 ; Yan et al, 2023 ). Yang et al found that GyH1 and CAV synergistically promote immunosuppression, pathogenicity, and viral replication in co-infected chicken, highlighting the interaction between CAV and GyH1 in the disease process and increasing potential health risk in the poultry breeding industry ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, other circoviruses have been reported, and several species have been shown to be pathogenic to poultry ( Truchado et al, 2019 ; Feher et al, 2022 ; Yan et al, 2023 ). Yang et al found that GyH1 and CAV synergistically promote immunosuppression, pathogenicity, and viral replication in co-infected chicken, highlighting the interaction between CAV and GyH1 in the disease process and increasing potential health risk in the poultry breeding industry ( Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before 2011, chicken infectious anemia virus ( CAV ) was the only member of the genus Gyrovirus within the family Circoviridae, which is responsible for severe anemia and immunosuppression in young susceptible chickens, and was one of the most important pathogens affecting the poultry industry and the SPF breeding industry ( Rijsewijk et al, 2011 ). Since 2011, a series of circovirus sequences similar to CAV (HGyV/AGV2, GyV3 through GyV13) have been reported ( Sauvage et al, 2011 ; Chu et al, 2012 ; Niu et al, 2019 ; Feher et al, 2022 ; Ji et al, 2022 ). These viruses have been identified in birds (chicken, northern fulmar, crested screamer, ashy storm petrel, ferruginous-backed antbird, white-plumed antbird, grey teal, pigeon, Pekin duck), mammals (human, cat, dog, ferret, mice) and reptiles (king rat snake) ( Feher et al, 2014 ; Truchado et al, 2019 ; Wu et al, 2019 ; Ji et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variability was demonstrated among sequences with a range of sequence identity of 92% to 97% when analyzing the VP1 gene. This level of sequence divergence may suggest that pheasants serve as true host species for the identified gyrovirus species, tentatively called Gyrovirus phaco 1 [17].…”
Section: Discussionmentioning
confidence: 99%
“…In some years, several pools were tested in parallel from the same locations (Table 1). In general, 89,199,122 reads were generated for these 20 samples using next-generation sequencing in a range of 1,419,265 to 17,507,704 sequence reads for each sample; of these, the specimen with the largest sequence data was available from a previous report and was reanalyzed in this study [17]. Sequence reads were analyzed using four metagenomic classifiers: Kraken, Kaiju, Centrifuge, and Virmine.…”
Section: Viral Flora Of the Pheasant Intestinementioning
confidence: 99%
“…CAV is found worldwide and causes significant mortality among chicks not protected by maternal antibodies. Other gyroviruses have been identified in diseased avian hosts, including in seabirds (1519). Herein, we describe a new gyrovirus associated with RDS in yellow-eyed penguins.…”
Section: Introductionmentioning
confidence: 99%